ANALISIS YURIDIS PELAKSANAAN PIDANA TAMBAHAN KEBIRI OLEH DOKTER BAGI PELAKU KEKERASAN SEKSUAL TERHADAP ANAK - Edwin Edwin; Yenny Fitri Z. (Universitas Wiralodra, 2025)
The Indonesian government issued the Government Regulation in Lieu of Law Number 1 of 2016 concerning additional castration penalties, becoming Law Number 17 of 2016. Since the issuance of the regulation, there have been several court decisions that have sentenced perpetrators of sexual violence against children to additional chemical castration penalties. However, legal problems arise when competent doctors openly refuse to be executors of chemical castration. This study focuses on: How is the regulation of the implementation of additional castration penalties by doctors for perpetrators of sexual violence against children? And what are the legal problems found in the additional castration penalty regulations for perpetrators of sexual violence against children? The research method used is a normative research method in the form of a bibliography. Hasil penelitian: there is a need to review Government Regulation Number 70 of 2020, because many articles are not clearly explained so as not to cause problems when chemical castration is carried out; and the problems of doctors who refuse to be chemical castration is carried out, and the unclear specialist doctors who have the competence to be executors.